The Role of Inclusive Leadership in Employee Readiness for Organizational Change: The Mediating Role of Leader Humor - Muhammed, Yazin Salim (Technium Social Sciences Journal, 2024)
The study examines the impact of inclusive leadership on employee preparedness for organizational change, focusing on the mediating role of the leader's sense of humor. This was accomplished by adopting the openness, availability, and accessibility characteristics of inclusive leadership in contrast to the workers' preparedness for organizational change in its cognitive, intention, and emotional dimensions. The leader's one-dimensional style of humor helps to strengthen this bond. A random sample of workers at Al-Abbas' Holy Shrine was chosen as a field of study using a questionnaire containing (156) persons in the research sample department. The (t) test was used to determine the correlation between two variables, while the (F) test was used to determine the significance of the regression model. The straightforward correlation coefficient (Spearman) was also employed. The relative quantity the independent variable contributes to explaining the dependent variable as a percentage was also determined using (R2). The researcher's most important finding is that inclusive leadership significantly influences workers' readiness for organisational change, as mediated by the leader's sense of humor. The study ended with several suggestions, including Al-Ameed University's emphasis on inclusive leadership, a key aspect of its work in general and employee preparedness for organisational change.